2022
DOI: 10.1001/jama.2022.9792
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fluid Bolus Administration on Cardiovascular Collapse Among Critically Ill Patients Undergoing Tracheal Intubation

Abstract: Key PointsQuestionIn critically ill adult patients undergoing tracheal intubation, does intravenous infusion of a crystalloid solution as a 500-mL fluid bolus decrease the incidence of severely low blood pressure, cardiac arrest, or death (referred to as cardiovascular collapse) during or shortly after the procedure?FindingsIn this randomized clinical trial that included 1065 critically ill adults, the incidence of cardiovascular collapse was 21.0% with administration of a fluid bolus vs 18.2% without administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 29 publications
1
32
0
Order By: Relevance
“…This global strategy including pre-intubation fluid infusion provided convincing results. However, two recent randomized controlled trials challenged the benefit of systematic fluid infusion before intubation to prevent PIHI in a non-selected population of critically ill patients [ 31 , 32 ]. A combination of tissue perfusion parameters and MAP, which increased the prediction of PIHI, may be of interest for tailored intervention and to limit fluid overload, associated with poor outcome in ICU [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…This global strategy including pre-intubation fluid infusion provided convincing results. However, two recent randomized controlled trials challenged the benefit of systematic fluid infusion before intubation to prevent PIHI in a non-selected population of critically ill patients [ 31 , 32 ]. A combination of tissue perfusion parameters and MAP, which increased the prediction of PIHI, may be of interest for tailored intervention and to limit fluid overload, associated with poor outcome in ICU [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that the amount of fluid given was very low, which can partially explain the results, and that it was not combined with systematic vasoactive support. Recently, a randomized controlled trial enrolling 1067 critically ill patients undergoing tracheal intubation [ 81 ] reported that administration of an intravenous fluid bolus alone without associated to a systematic administration of norepinephrine compared with no fluid bolus did not significantly decrease the incidence of cardiovascular collapse. The FLUVA trial (NCT05318066) is currently underway to assess the effect of fluid loading and introduction of vasopressors before the tracheal intubation to reduce severe cardiovascular collapse.…”
Section: Hemodynamic Optimization and Choice Of Drugsmentioning
confidence: 99%
“…This is consistent with previous randomized trials comparing alternative approaches to tracheal intubation commonly used in clinical care. 28,38,39,[45][46][47][48][49][50] This approach was approved by the US Department of Defense (DoD) Defense Health Agency Human Research Protection Office (EIRB# 944893).…”
Section: Waiver Of Informed Consentmentioning
confidence: 99%